Diversity and microbiological quality of fruit juices produced in southern Benin - Noumavo, Agossou Daniel Pacôme; GLODJINON, Nicéphore; Ohin, Brice M.; DOGNON, ELAVAGNON DOROTHE; SALAKO, Valère; HOSSOU, DOSSOU FIRMIN; BABA-MOUSSA, LAMINE; BABA-MOUSSA, FARID A. KADER SAÏD (My University, 2023)
The fruit juice production sector is growing rapidly in Benin's major urban centers and appears to have enormous hygienic insufficiencies. This study aimed to identify and evaluate the microbiological quality of the different fruit juices produced in southern Benin. The methodological approach to the first objective consisted of a semi-structured survey coupled with direct observations of fifty enterprises produced fruit juices in the Municipalities of Cotonou and Abomey-Calavi. The microbiological quality evaluation of pineapple juice (Ananas cosmosus) consisted in the enumeration of microorganisms that alter both hygienic and market ability qualities of foodstuffs, using standard methods. This study revealed a strong diversity of fruit juices. There are thirteen (13) different mono-fruity juices, fifteen (15) poly-fruity juices with pineapple and nine (09) poly-fruity juices without pineapple. The pineapple mono- fruity juice is produced by almost all the enterprises (98%). Poly-fruity juices with pineapple are the most popular among consumers. From the microbiological point of view, a strong variation of the microbial load was noticed from one enterprise to another. With the exception of a few enterprises, about 18% of pineapple juices are microbiologically non-compliant. These pineapple juices contain mycotoxigenic yeasts and moulds, lactic acid bacteria, thermotolerant coliforms and Staphylococcus aureus. The consumption of these poor sanitary quality juices poses a real public health problem, as it exposes consumers to the severe food poisoning risks.
Keywords: Fruit juice; diversity; pineapple; Ananas cosmosus; microbiological quality; non-compliance.